Karakteristik lelah baja poros Din 42CrMo4 (gandar lokomotif) bertakik U dan V akibat beban amplitudo konstan dan beban tiba-tiba - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This research aims to investigate fatigue strength of notched shaft under cyclic loading. The material used in this research was shaft steel VCL DIN 42 CrM04. It were tensile test specimens and Vand U notched tensile test specimens. Normal test specimens were tested in a tensile test machine to find ultimate and yield strength. The notched specimens were tested in a rotary bending machine to find fatigue strength. The results show that the fatigue strength ofU and V notched specimens are 215 MPa and 225MPa respectively. The fatigue strength of U and V specimens under combination cyclic loading are 146 MPa and 132 MPa respectively.